Five macrocyclic glycosides from Schoenoplectus tabernaemontani. Issue 3 (1st February 2019) - Peng, Dian; Lin, Xiaolin; Jiang, Lin; Huang, Juan; Zeng, Guangyao; Deng, Xu; Zhou, Yingjun
Abstract: Macrocyclic glycosides with unique 22-membered dimeric lactone skeleton, are rare occurring natural products. There are only ten compounds reported so far. Herein we reported the isolation and characterisation of five macrocyclic glycosides from Schoenoplectus tabernaemontani, including three new compounds (Schoenopolide A-C, 1–3) and two known ones, Berchemolide (4 ) and Clemoarmanoside B (5 ). Their structures were established on the basis of extensive analysis of spectroscopic data. In addition, the anti-oxidative activity of Berchemolide (4 ) against H2 O2 -induced of renal tubular epithelial (HK-2) cells was also evaluated. Abstract :